2013
DOI: 10.1128/jcm.00494-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Achromobacter Isolates from Cystic Fibrosis and Non-Cystic Fibrosis Patients in Madrid, Spain

Abstract: bMultilocus sequence typing and nrdA sequence analysis identified 6 different species or genogroups and 13 sequence types (STs) among 15 Achromobacter isolates from cystic fibrosis (CF) patients and 7 species or genogroups and 11 STs among 11 isolates from non-CF patients. Achromobacter xylosoxidans was the most frequently isolated species among CF patients.A chromobacter spp. are nonfermenting, Gram-negative rods that are widely distributed in nature, some of which are associated with opportunistic infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
31
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 20 publications
11
31
0
2
Order By: Relevance
“…A similar diversity was observed in the USA (14 different Achromobacter species and genogroups from 341 CF patients) [15], in Spain (six different species and genogroups from 14 CF patients) [16], in the UK (12 species and genogroups from 96 CF patients) [17] and in France (11 species and genogroups from 47 CF patients) [18]. In congruence with these studies, A. xylosoxidans was the Achromobacter sp.…”
supporting
confidence: 79%
“…A similar diversity was observed in the USA (14 different Achromobacter species and genogroups from 341 CF patients) [15], in Spain (six different species and genogroups from 14 CF patients) [16], in the UK (12 species and genogroups from 96 CF patients) [17] and in France (11 species and genogroups from 47 CF patients) [18]. In congruence with these studies, A. xylosoxidans was the Achromobacter sp.…”
supporting
confidence: 79%
“…Studies have attributed persistent Achromobacter infections predominantly to A. xylosoxidans (2,11,12,18), with a few exceptions, including A. insuavis and A. dolens (5,6). We now know that this may represent a broader species distribution.…”
Section: Discussionmentioning
confidence: 98%
“…Two small single-center studies found that all patients were infected with unique Achromobacter strains (20,21). Conversely, several studies (both single and multicenter) have suggested that shared strains do exist (2,12,18,19,24,25,27,33,(43)(44)(45)(46)(47)(48), with common strains accounting for 5 to 50% of total Achromobacter infections. Additionally, chronic infection was most commonly due to persistence of the original infecting strain (14,19,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…xylosoxidans is an important emerging pathogen among CF patients worldwide, commonly described as an environmental pathogen widely distributed in soils and waters (4,14,34,35). Nevertheless, this statement is not supported by any study in natural environments.…”
Section: Discussionmentioning
confidence: 98%